ENTREPRENEURSHIP AND EDUCATION IN THE EUROPEAN UNION - STUDENTS' PERCEPTION ON THE SUBJECT - Saraiva, Helena (2018)
In this study has been tried to found evidence that entrepreneurship education has impact on students' behavior and perception of its effects. As a consequence, entrepreneurship education also impacts the economic development of many European Union (EU) countries. In the first part of the text, a brief characterization on the EU entrepreneurship education system has been presented. Subsequently, an analysis of data from various publications and reports, with relevance in the subject area has been performed, in order to assess if there is a relationship between entrepreneurship education and the results obtained by the same process, in terms of students’ perceptions. We found evidence that entrepreneurship education assumes an impact on the entrepreneurial intention on young entrepreneurs.